2011
DOI: 10.1177/003335491112600213
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety Perceptions and Practices of Older Adults

Abstract: SynopSiSobjectives. Older adults are considered more vulnerable to foodborne illness due to lowered immune function. We compared the food safety perceptions and practices of older and younger adults and determined associations with demographic characteristics.Methods. We focused on 1,317 participants 60 years of age from the U.S. Food and Drug Administration's 2006 Food Safety Survey, a telephone survey of a nationally representative sample of American consumers. We used data on participants 60 years of age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 21 publications
3
38
0
Order By: Relevance
“…Females were more concerned, more likely to reduce seafood consumption and more likely to be influenced by all forms of media when compared with males. This is similar to findings by Anderson et al (2011) in which women showed better food safety practices and were more aware of food safety risks compared to males. Other researchers have found that women were more likely to have higher levels of concern for food safety than men (Knight and Warland 2004).…”
Section: Gender and Age Perception Differencessupporting
confidence: 88%
“…Females were more concerned, more likely to reduce seafood consumption and more likely to be influenced by all forms of media when compared with males. This is similar to findings by Anderson et al (2011) in which women showed better food safety practices and were more aware of food safety risks compared to males. Other researchers have found that women were more likely to have higher levels of concern for food safety than men (Knight and Warland 2004).…”
Section: Gender and Age Perception Differencessupporting
confidence: 88%
“…In addition, individuals with higher levels of education may be more willing to accept products that are modified to increase safety, such as irradiated beef (73). However, low SES individuals are more likely to recognize that home food preparation can be a risky activity for foodborne disease, are more likely to think refrigerator temperature is important, and are more likely to have general knowledge about appropriate food-related hygiene (16, 44, 45). …”
Section: Discussionmentioning
confidence: 99%
“…To establish the influence of factors determining respondents' application of preventive measures during the outbreak (dependent variable), we performed stepwise backward regression analyses. Following [22][23][24], we included the following independent variables in the initial model: the demographics age, education, income and sex, and the factors perceived severity of a Salmonella infection, perceived severity of the outbreak, knowledge about Salmonella infections, and increased general kitchen hygiene during the outbreak. Education was recoded into a new variable with three options: Low, middle or high, while sex was included in the regression analyses as a dummy variable.…”
Section: Analysesmentioning
confidence: 99%